Comparison of the lethal effects of chemical warfare nerve agents across multiple ages. (22nd January 2016) - Wright, Linnzi K.M.; Lee, Robyn B.; Vincelli, Nicole M.; Whalley, Christopher E.; Lumley, Lucille A.
Highlights: Children may be more vulnerable than adults to chemical warfare nerve agents (CWNA). We estimated the 24 h LD50 for seven CWNA in rats at six times in development. Perinatal and adult rats were more susceptible than pubertal rats to the G-agents. Age-related differences were not observed in rats for the V-agents. Abstract: Children may be inherently more vulnerable than adults to the lethal effects associated with chemical warfare nerve agent (CWNA) exposure because of their closer proximity to the ground, smaller body mass, higher respiratory rate, increased skin permeability and immature metabolic systems. Unfortunately, there have only been a handful of studies on the effects of CWNA in pediatric animal models, and more research is needed to confirm this hypothesis. Using a stagewise, adaptive dose design, we estimated the 24 h median lethal dose for subcutaneous exposure to seven CWNA in both male and female Sprague-Dawley rats at six different developmental times. Perinatal (postnatal day [PND] 7, 14 and 21) and adult (PND 70) rats were more susceptible than pubertal (PND 28 and 42) rats to the lethal effects associated with exposure to tabun, sarin, soman and cyclosarin. Age-related differences in susceptibility were not observed in rats exposed to VM, Russian VX or VX.